DEFINITIONS OF VIOLENCE AGAINST WIVES AMONG INDONESIAN SOCIAL WORK COLLEGE STUDENTS - Binahayati Rusyidi (Lembaga Penelitian Universitas Pasundan, 2017)
Violence against wives is the most common form of violence against women reported in Indonesia. Understanding the definition of violence against wives is one of first steps to address the problem given that recognition about what constitutes violent behaviors has an influence on how society responds to victims and perpetrators. The study described and examined factors associated with the attitudes of Muslim undergraduate social welfare students toward definitions of violence against wives using socio-demographic and socio-cultural perspectives. Samples were selected non-randomly using convenience sampling techniques. Data were collected through a self-administered survey taken by 275 students in the social welfare department of two separate universities located in the provinces of Yogyakarta and East Java late 2016. Data was analyzed using hierarchical regressions techniques. The study found that students generally reported stronger agreement to viewing physical violence as a form of violence against wives. On the contrary, they were less likely to view non-physical violence as violent behavior. Gender, attitudes toward gender roles, and type of university were found to be associated with attitudes toward the definition of violence against wives. Implications from the findings were discussed, taking into account the roles of educational institutions in shaping the students’ attitudes.